Flame Photometric Determination of Traces of Sodium Content of the Sea Water Sample - PATIL, C.S.; ARBAD, B.R. (Asian Journal of Chemistry, 2010)
Sea water sample is collected, taking all necessary precautions like container material, depth of the sea, temperature of the sample during collection, pH and dissolved oxygen etc. and analysed in the laboratory for its sodium content. An alkali metal which gives intensely yellow colour flame when aspirated into the flame.